2013
DOI: 10.1021/jm400587g
|View full text |Cite
|
Sign up to set email alerts
|

8-Benzamidochromen-4-one-2-carboxylic Acids: Potent and Selective Agonists for the Orphan G Protein-Coupled Receptor GPR35

Abstract: 8-Amido-chromen-4-one-2-carboxylic acid derivatives were identified as novel agonists at the G protein-coupled orphan receptor GPR35. They were characterized by a β-arrestin recruitment assay and optimized to obtain agonists with nanomolar potency for the human GPR35. The compounds were found to exhibit high selectivity versus the related GPR55. The most potent agonists were 6-bromo-8-(4-methoxybenzamido)-4-oxo-4H-chromene-2-carboxylic acid (85, EC50 12.1 nM) and 6-bromo-8-(2-chloro-4-methoxybenzamido)-4-oxo-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 53 publications
0
81
0
Order By: Relevance
“…These ligands, although also active at GPR35, displayed marked differences in potency between the rat and human orthologs, a feature previously noted for zaprinast (Taniguchi et al, 2006;Jenkins et al, 2010). The published literature indicates that certain GPR35 agonists such as pamoate (Jenkins et al, 2010), 4-{(Z)-[(2Z)-2-(2-fluorobenzylidene)-4-oxo-1,3-thiazolidin-5-ylidene]methyl}benzoic acid , and various 8-benzamidochromen-4-one-2-carboxylic acids (Funke et al, 2013) are highly selective for the human ortholog, whereas others such as pemirolast and amlexanox are highly selective for the rat ortholog. Although it is clearly speculative, it may be interesting to consider whether the inability to progress various antiallergics in the clinic may have a basis in this species selectivity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These ligands, although also active at GPR35, displayed marked differences in potency between the rat and human orthologs, a feature previously noted for zaprinast (Taniguchi et al, 2006;Jenkins et al, 2010). The published literature indicates that certain GPR35 agonists such as pamoate (Jenkins et al, 2010), 4-{(Z)-[(2Z)-2-(2-fluorobenzylidene)-4-oxo-1,3-thiazolidin-5-ylidene]methyl}benzoic acid , and various 8-benzamidochromen-4-one-2-carboxylic acids (Funke et al, 2013) are highly selective for the human ortholog, whereas others such as pemirolast and amlexanox are highly selective for the rat ortholog. Although it is clearly speculative, it may be interesting to consider whether the inability to progress various antiallergics in the clinic may have a basis in this species selectivity.…”
Section: Discussionmentioning
confidence: 88%
“…4B). We and others have reported that many compounds first identified as ligands at human GPR35, including zaprinast, display markedly different potency and/or activity at rodent orthologs (Taniguchi et al, 2006;Jenkins et al, 2010Jenkins et al, , 2012Funke et al, 2013;Neetoo-Isseljee et al, 2013). We next examined the activity of a variety of mast cell stabilizers at the rat ortholog of GPR35 in the BRET-based b-arrestin-2 interaction assay.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-throughput systems, expression of a chimeric G protein a subunit switches the preference of GPR35 from G i/o or G s to G q , and, consequently, evokes a rise in the level of inositol phosphate and intracellular Ca 2+ , each serving as a readout for receptor activation [2,7,20,21]. These assays, which are efficient, convenient, and allow rapid screening of large numbers of molecules led to the identification of a battery of pharmacological tools essential for identification of functional GPR35s [12,13,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Chromone-based drugs exhibit anticancer, anti-HIV, antioxidant, antiinflammatory, analgesic, antimicrobial, antimalarial, anti-diabetic, anticonvulsant, antiplatelet, gastroprotective, antihistaminic, antihypertensive, and insecticidal activity [4,5]. The chromen-4-one core has recently been identified as a potent and selective orphan G proteincoupled receptor (GPR35) agonist [6] in which, according to 3D-QSAR studies [7], steric, electrostatic, and hydrophobic substituents play a significant role. The substitution of a chemical system by a group is the most important fundamental modification in the search for new molecular properties.…”
Section: Introductionmentioning
confidence: 99%